1989
DOI: 10.1007/bf00047339
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cells and liver metastasis

Abstract: Kupffer cells, tissue-fixed macrophages located in the sinusoids of the liver, represent the highest concentration of mononuclear phagocytes in the body. Their ability to act as scavengers of particulate material in the blood has given rise to speculation that they play a role in controlling hepatic metastases derived from blood-borne tumor cells. Circumstantial evidence for such a role has been obtained from animal studies where Kupffer cell function has been compromised or inhibited, and from anecdotal clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 91 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…The liver is the largest reticuloendothelial organ in the body, with Kupffer cells making up over 80% of the body's fixed macrophage population [20]. Previous studies have shown that Kupffer cells possess considerable tumoricidal activity against a variety of tumor cell targets [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the largest reticuloendothelial organ in the body, with Kupffer cells making up over 80% of the body's fixed macrophage population [20]. Previous studies have shown that Kupffer cells possess considerable tumoricidal activity against a variety of tumor cell targets [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, activated Kupffer cells still leave a residual burden of tumor cells that can continue to metastasize. As the hepatic tumor load increases the Kupffer cell population within tumor vessels decreases [6]. Kupffer cell depletion is thought to be a factor in the development of hepatocellular carcinoma [41] and in the formation of carcinogeninduced hepatic nodules that eventually become carcinomas [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Kupffer cells and other macrophages can be activated to a tumoricidal state by administering biological response modifiers (BRMs) such as lipopolysaccharide [11][12][13]20], gamma interferon [11,12,21,22] and muramyl peptides [6,7,20,23,24] resulting in reduced tumor load and increased survival time. The close proximity of Kupffer cells to liver metastases makes them an attractive target for immunomodulatory therapy to stimulate macrophage defense [7,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations